A world key to the species of Pyxine with lichexanthone, with a new species from Brazil - Aptroot, Andre; Jungbluth, Patricia [UNESP]; Caceres, Marcela E. S. (Cambridge Univ Press, 2014)
A world key is given to the species of Pyxine with lichexanthone in the upper cortex. Pyxine pustulata Aptroot & Jungbluth is described as a new corticolous species of Pyxine from Sao Paulo State in Brazil, with lichexanthone in the cortex, upper surface K-, a yellow to ochraceous medulla and clusters of laminal polysidiangia. Brazil is clearly the centre of Pyxine diversity, with 34 out of c. 70 species known worldwide.
Keywords: lichen; Physciaceae; Sao Paulo; systematics; taxonomy; tropical